Penguatan Kompetensi Digital Bagi Tuna Karya dan Remaja Putus Sekolah di Kelurahan Wonorejo - Sulistiowati; Julianto Lemantara; Ayouvi Poerna Wardhanie; Lilis Binawati; Tony Soebijono (Jurnal Ragam Pengabdian, 2025)
The digital competency strengthening program for school dropouts and unemployed youth in Wonorejo Village is a strategic effort to improve the quality of human resources in the digital era. This activity aims to equip participants with practical skills in Microsoft Office and productive internet use, as a foundation for entering the workforce and entrepreneurship. The training was conducted offline using the Direct Instruction method, where instructors delivered material in a structured manner through explanations, demonstrations, guided practice, and independent practice. The program was evaluated by distributing questionnaires to 18 training participants to assess its effectiveness. The results showed an average score of 4.58 on a five-point scale, falling into the "tend to strongly agree" category. This indicates that the Microsoft Office and internet use training was well implemented and had a positive impact on improving participants' skills and confidence. This program not only strengthens technical skills but also plays a crucial role in empowering school dropouts and unemployed youth to be more adaptable and competitive in facing the challenges of the digital workplace.